2002
DOI: 10.1002/1522-2675(200205)85:5<1479::aid-hlca1479>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hybridization Properties of an Oligonucleotide Consisting of 1′,4′-Anhydro-2′,5′-dideoxy-2′-(thymin-1-yl)-D-altritol

Abstract: The novel oligonucleotide analogue 7, consisting of 1',4'-anhydro-2',5'-dideoxy-2'-(thymin-1-yl)-d-altritol (4), residues was synthesized by the phosphoramidite approach on an automated DNA synthesizer. The phosphoramidite building block 6 was obtained by phosphitylation of the corresponding isonucleoside 5. Oligoisonucleotide 7 contains an extended phosphodiester linkage with a higher flexibility. Oligoisonucleotide 7 was studied with respect to hybridization properties, enzymatic stability, and CD spectra. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In our previous reports for synthesis and incorporation of isonucleosides into antisense oligos, we found that modified antisense oligos not only possess strong nuclease resistance but more interestingly become good substrates of RNase H (20). CD spectra and molecular modeling demonstrated that isonucleoside-modified DNA duplexes still adopt a B-like conformation, but the formation of Watson-Crick hydrogen bonding was perturbed by the torsion of the backbone (21,22), while isonucleosidemodified oligonucleotide/RNA duplex formed an A-like conformation in solution (23). An introduction of an amino group into the isonucleoside may increase the thermal stability of the isonucleoside-modified oligonucleotide with its complementary sequence.…”
Section: Introductionmentioning
confidence: 92%
“…In our previous reports for synthesis and incorporation of isonucleosides into antisense oligos, we found that modified antisense oligos not only possess strong nuclease resistance but more interestingly become good substrates of RNase H (20). CD spectra and molecular modeling demonstrated that isonucleoside-modified DNA duplexes still adopt a B-like conformation, but the formation of Watson-Crick hydrogen bonding was perturbed by the torsion of the backbone (21,22), while isonucleosidemodified oligonucleotide/RNA duplex formed an A-like conformation in solution (23). An introduction of an amino group into the isonucleoside may increase the thermal stability of the isonucleoside-modified oligonucleotide with its complementary sequence.…”
Section: Introductionmentioning
confidence: 92%
“…Besides, the conformational alteration would also have an influence on the hybridization properties of the siRNA duplex, as well as its recognition by other proteins, such as the kinds of nucleases and RNA binding proteins. Isonucleosides (IsoNA) are a novel kind of nucleoside analogue in which the nucleobase is linked to another position of ribose other than C-1′. , In our previous work, we showed that the modified oligonucleotides d -/ l -isoNA 1 and 2 (Figure ) could form a stable duplex with DNA or RNA with a characteristic tertiary conformation as the normal unmodified DNA/RNA duplex. …”
Section: Introductionmentioning
confidence: 99%
“…179 (idT) 13 -dT oligonucleotides containing an extended phosphodiester linkage via the incorporation of 2′,5′-anhydro-3′deoxy-3′-(thymin-1-yl)-D-altritol building blocks (o7) can form stable duplexes with (dA) 14 but with a much reduced T m (28.8 °C vs 35.5 °C for (dT) 14 •(dA) 14 ). 180 With RNA (A 14 ), a more stable duplex (T m of 31.5 °C) can be obtained. CD spectra indicate that duplexes are formed (A-form with RNA).…”
Section: Isonucleic Acids (Inas)mentioning
confidence: 99%
“…166 (idT) 13 -dT oligonucleotides containing D-arabinitol-, L-arabinitol-, or D-altritol-modified T nucleotides (o7) show no degradation by SVPDE after 30 min. 172,180 When D-arabinitol-modified A and T nucleotides (o1) are introduced into the d(GTAGAATTCTAC) sequence, both the SVPDE and the calf spleen phosphodiesterase (a 5′−3′exonuclease) resistances increase with an increasing number of modified nucleotides. 165 The (idAdT) 6 -dT sequence containing the D-arabinitol-modified A nucleotide is very resistant to exonuclease digestion and only shows 20−30% degradation after 100−120 h. The dinucleotides pidApdC and pdCidU containing the D-arabinitol A or U building blocks show an increased stability to exonucleases, with pdCidU totally resistant to phosphodiesterase cleavage.…”
Section: Isonucleic Acids (Inas)mentioning
confidence: 99%
See 1 more Smart Citation